Research on the involment of phenoloics in the defence of horticultural plants - Ana SLATNAR; Maja MIKULIČ-PETKOVŠEK; Robert VEBERIČ; Franci ŠTAMPAR (Acta Agriculturae Slovenica)
Phenolic compounds are not directly involved in the primary metabolism of plants but possess a number of important roles: (1) serving as attractants for pollinators and various animals, involved in the transfer of seeds, (2) plant protection from herbivores and against pathogen infection, (3) defining plant-plant relationships and the symbiosis between plants and microbes. The present review of our research work stresses the role of phenolic compounds in the defense mechanism against different fungi and bacteria. It has been established, that the content of phenolics is greatly affected by the infection with pathogenic organisms. Studies on several horticultural plants have demonstrated that the response to infection differs among the analyzed plant species. Generally, an increase of phenolic compounds can be expected in tissues near the infection site. The comparison of healthy and infected tissue reflects an increase of phenolics in infected tissues. Higher levels of all analyzed phenolic groups have been measured in the latter, with the exception of the anthocyanins. Based on the findings of many-year research studies, it can be concluded that phenolic compounds are involved in the plant defense mechanisms, but the response varies among species.